irpll Curricula and learning of early days schools in Pashto language: whatever, priority,hardship,negligent,consequences - jan, abdullah (JPL, 2023)
Children are the important and valuable part of society, which has its own special position and they should have this high position in any society. A child also have emotion, feeling, love and wishes whatever the people’s rights is, children are equally included. In today’s world children’s education should be more important than any other government agenda, since they are our future’s asset therefor, attention to children education should be number one priority of any government. Moreover they should be thought all ethical values; compassion and rights of others etc. so later in life, they don’t run to any difficulty or problems. The parents and education official should take the responsibility to manage proper education so they don’t have hardship in the future and facilitate the prose of children’s education to complete it. Children are the foundations and base of any society if the responsible people don’t pay attention to this matter then they will face consequences of negligent later on since you can’t build a solid building on the swamp.